Molecular Testing on Cytology for Gene Fusion Detection - Schmitt, Fernando; Di Lorito, Alessia; Vielh, Philippe (Frontiers in Medicine, 2021)
Cytological samples are an appropriate first approach to obtain material in impalpable lesions and/or in patients unsuitable for surgical procedures. Although cytology has intrinsic limitations, the cell block method has enhanced the diagnostic rate and the possibility of achieving an accurate diagnosis. In clinical practice, an increasing interest has regarded the application of molecular technologies on cytological material. In particular, in the last years, detection of gene fusions as well as mutations on cytological samples are becoming mandatory. Different technologies are available such as immunocytochemistry, reverse transcription-polymerase chain reaction, fluorescence in situ hybridization and massive parallel sequencing approaches. Considering the new targeted drugs, cytological samples can be of use to detect gene fusions not only in lung carcinomas but also in other solid and lymphoproliferative tumor patients.